Numerical Solutions of Fourth-order Singular Boundary Value Problems by New Modified Adomian Decomposition Method - AL-Rabahi, Zainab Ali Abdu; Yahya Qaid Hasan (IJRDO -JOURNAL OF MATHEMATICS, 2020)
In this work, we apply Modified Adomian decomposition method (MADM) to solving fourth-order singular boundary value problems. The suggested method can be applied to linear and nonlinear problems. The planner is checked for some examples and the obtained results statement competence of the suggested method.